2009
DOI: 10.1111/j.1740-0929.2009.00664.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of the amino acid motifs of BoLA‐DRB3 alleles with mastitis pathogens in Japanese Holstein cows

Abstract: The association of the polymorphism of bovine leukocyte antigen (BoLA-DRB3) genes, identified by the polymerase chain reaction sequence-based typing (PCR-SBT) method, with resistance and susceptibility to mastitis caused by Streptococci, coagulase-negative Staphylococci, Escherichia coli and Staphylococcus aureus was investigated. Blood samples for DNA extraction were collected from 170 Holstein cows (129 mastitis and 41 healthy cows) from 5 districts in Chiba prefecture, Japan. Susceptibility or resistance to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 31 publications
2
6
0
Order By: Relevance
“…Indeed it has been shown that Arg 71 in P4 is correlated with resistance to persistent lymphocytosis caused by the bovine leukemia virus (42). Furthermore, Arg 71 in P4 has been associated with a high resistance to Escherichia coli mastitis in dairy cows (43). Our results appeared to strengthen previous studies suggesting that amino acid residues in P4 are crucial for resistance and/or susceptibility to diseases (34).…”
Section: Discussionsupporting
confidence: 88%
“…Indeed it has been shown that Arg 71 in P4 is correlated with resistance to persistent lymphocytosis caused by the bovine leukemia virus (42). Furthermore, Arg 71 in P4 has been associated with a high resistance to Escherichia coli mastitis in dairy cows (43). Our results appeared to strengthen previous studies suggesting that amino acid residues in P4 are crucial for resistance and/or susceptibility to diseases (34).…”
Section: Discussionsupporting
confidence: 88%
“…The frequency of an MHC allele or group of alleles might become increased in cattle populations having the same selective pressures imposed by similar production systems, even in different geographic locations. From the analysis of previously published data (Takeshima et al, 2015a), we found that Holstein populations were enriched with alleles reported to be associated with resistance (BoLA-DRB3*011:01 and BoLA-DRB3*012:01) and susceptibility (BoLA-DRB3*001:01 and BoLA-DRB3*015:01) to mastitis (Yoshida et al, 2009b;Yoshida et al, 2009a). The Holstein breed has been submitted to intense selective pressure due to milk production traits which can make it susceptible to mastitis but, at the same time, there is also pressure for selecting resistant individuals.…”
Section: Discussionmentioning
confidence: 94%
“…On the other hand, other issues like production traits improvement, resistance to mastitis pathogens, somatic cell counts and milk yield have also been related to specific BoLA alleles (DIETZ et al, 1997;RUPP et al, 2007;YOSHIDA et al, 2009;BALTIAN et al, 2012;YOSHIDA et al, 2012). However, some controversies exist between different studies.…”
Section: Discussionmentioning
confidence: 99%
“…These genes are associated with genetic resistance and susceptibility to a wide range of diseases, including mastitis (DIETZ et al, 1997;RUPP et al, 2007;YOSHIDA et al, 2009;YOSHIDA et al, 2012), dermatophilosis (MAILLARD et al, 2002), tick-borne diseases (DUANGJINDA et al, 2013), infection with Neospora caninum (SCHWAB et al, 2009), African trypanosome species (KARIMURIBO et al, 2011), and Theileria annulata (GLASS et al, 2012b). Moreover, BoLA appears to influence other traits such as milk yield, growth and reproduction, and variations in immune responses to antigens (TAKESHIMA; AIDA, 2006) and even vaccine peptides (GARCIA-BRIONES et al, 2000;GLASS et al, 2012a).…”
Section: Introductionmentioning
confidence: 99%